2011
DOI: 10.5251/abjna.2011.2.2.244.249
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and seed characteristics among selected Parkia biglobosa (JACQ) G. Don. Population

Abstract: Fruit Characteristics (pod length, number of pod per bunch, pulp and seed weight, pulp weight and pod breadth), Seed Characteristics (number of seed per bunch, expected seed number per pod and seed weight per bunch), and Qualitative Characteristics of seeds (seed colour, shape, size and texture) of Parkia biglobosa (Jacq) G. Don population were investigated in this study. Twenty six (26) P. biglobosa population were sampled at the permanent site of the University of Ilorin, Nigeria, in May 2010 and fruits were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…This agrees with the observation of Hopkins (1983) and Olorunmaiye et al (2011). The seeds with brown seed coat germinated earlier than the dark-black, which suggests easier water penetration by the former and required no pretreatment of seeds.…”
Section: Materials Usedsupporting
confidence: 91%
“…This agrees with the observation of Hopkins (1983) and Olorunmaiye et al (2011). The seeds with brown seed coat germinated earlier than the dark-black, which suggests easier water penetration by the former and required no pretreatment of seeds.…”
Section: Materials Usedsupporting
confidence: 91%
“…This is in agreement with the report of Abagale et al [27], who discovered the presence of saponin, glycoside, flavonoids, tannin and polyphenols in P. biglobosa pod husk. Olorunmaiye et al [28] also reported the use of the pod husk in producing an insecticide powder or dust which is used in protecting crops from insect pests.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that, one of the challenges of indigenous tree species regeneration is inadequate knowledge of the condition necessary for their germination and seedling production techniques (Sale, 2015;Mukhtar, 2016). P. biglobosais an important indigenous multipurpose tree species providing food, medicines and shade while stabilizing degraded environment and playing ecological role in nutrient cycling (Olorunmaiye et al, 2011;Adejumo et al, 2013;Oluwafemi et al, 2014). Information on growth and development of indigenous tree species is an important pre-requisite for sustainable utilization and regeneration of multipurpose tree species like P. biglobosa.…”
Section: Introductionmentioning
confidence: 99%